The area parameters of settling of the Upper Prut River basin - Krool, Galina; Krool, Volodymyr; Gadelshyn, Oleksandr (Suceava, Romania, 2015)
There are three groups of values: quantitative parameters of settlements, areal land and demographic are offered to determine ekistic situation in the Prut river basin (within 35 landscape regions). The first group (the amount of settlements, the density of settlements, index or coefficient of territorial concentration of settlements (Ktcp), or coefficient of uniformity of settlement‟s distribution are suggested in the previous findings. The majority of parameters like the area of district, the area of settlement, the area of the average settlement, and the level of settling constitute the second group. The latter parameter is determined by the part of the landscape region that is occupied by the settlements. Finally, the third group is the most numerous by the quantity of parameters. They are the demographic potential of territory (in our case landscape region), the population density, the average geometric density of population in the settlement, the average geometric population in the settlement, and the coefficient of uniformity of the population distribution. The study concerns peculiarities of the settlement structure of the Upper Prut river basin on the basis of the areal parameters of settlements. The final assessment in the form of four parameters is fulfilled with the help of the rating analysis. Meanwhile, the sum of the rating values of the district area, the settlement area, the area of settling of landscape region and the area of average settlement varies from 13 (the minimum – 4) up to 131 (the maximum up to 132). While the average geometric value of the rating parameters is 58.8 points, the average interval for areal parameters lies within 50-69 points. Landscape regions with the sum of rating points within the proposed frame are distinguished with the settlement network that is currently optimal. Insignificant development of the settlement network can be indicated if the sum of the rating points tends to increase (≥70 points). In the case of the sum within 70-89 points, the settlement structure will be noticed for the slightly insufficient space structure.
Keywords: quantitative parameters of settlements; potential of territory; Prut river basin